2021
DOI: 10.5294/aqui.2021.21.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risks and job satisfaction: A meaningful relationship for oncology workers

Abstract: Objective: To determine the relationship between psychosocial risk factors and professional satisfaction of workers working in oncology and palliative care units in a region of Chile. Material and Method: Non experimental, cross-sectional, correlational study with quantitative approach. In the last semester of 2016, the census of health workers was carried out, using an instrument composed of three parts for data collection: a) bio-sociodemographic history, b) SUSESO-ISTAS 21 questionnaire for psychosocial ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…In our study we observed a significant association between most of the psychosocial dimensions and the degree of job satisfaction ( Table 4 ), with the exception of support and level of social relationships. A similar behavior occurs in the group of construction workers ( Sáenz, 2016 ); however, in other activities of evident social and affective involvement, such as the group of workers in oncology units, social support, level of social relationships and quality of leadership are very important aspects in their degree of job satisfaction ( Rivera-Rojas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study we observed a significant association between most of the psychosocial dimensions and the degree of job satisfaction ( Table 4 ), with the exception of support and level of social relationships. A similar behavior occurs in the group of construction workers ( Sáenz, 2016 ); however, in other activities of evident social and affective involvement, such as the group of workers in oncology units, social support, level of social relationships and quality of leadership are very important aspects in their degree of job satisfaction ( Rivera-Rojas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have analyzed in depth the psychosocial burden in classic sectors such as teaching ( Galdeano et al, 2007 ; Gutiérrez-Bedmar et al, 2009 ), healthcare ( Stoddard et al, 2001 ; Hamdan-Mansour et al, 2011 ; García-Rodríguez et al, 2015 ; Miller et al, 2018 ), and social workers ( Rodriguez-Alonso et al, 2017 ; Rivera-Rojas et al, 2021 ), profiles that are characterized by suffering a higher degree of stress. However, studies in unique sectors are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This study makes use of the SUSESO/ISTAS 21 questionnaire in its brief version, which was adapted and validated in Chile by the School of Public Health of the University of Chile. This questionnaire allows identifying and measuring the existence of psychosocial risk, and has been used in multiple studies in the health sector (Rivera-Rojas, Ceballos-Vásquez & González-Palacios, 2021). It has proven to be globally reliable, inexpensive to apply, and promising, although its validity in various populations is unknown (Mendoza-Llanos & Moyano-Díaz, 2019), as is the case in Colombia.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Ciertamente en el aspecto intralaboral, derivados de la organización y división del trabajo, se apreció que el personal médico presentó una baja demanda con bajo control, poco apoyo social por parte de sus jefes inmediatos y poca recompensa, por lo cual, según el modelo demanda-control-apoyo social el tipo de trabajo que realizan estos trabajadores es un Trabajo Pasivo. Caso contrario a los resultados arrojados por Rivera et al (14) (2021), donde investigaron a trabajadores del área de oncología, reportando ser un trabajo activo con buena recompensa, esto se debe a que estas áreas de servicio son muy demandantes, con altos ritmos de trabajo, sobrecarga mental y emocional. En cambio, en esta investigación el personal de salud en su mayoría realiza funciones administrativas, y como es un trabajo pasivo, puede estar generando en la misma monotonía, afectando gradualmente la satisfacción en su entorno laboral.…”
Section: Discussionunclassified
“…Por lo que se refiere a los factores psicosociales y estrés laboral, estos constituyen uno de los temas más abordados en las últimas décadas por el impacto que genera en la salud y el bienestar de las y los trabajadores, es por ello que, existen numerosas investigaciones a nivel mundial que abordan esta temática de estudio. (11,12,13,14,15) Sin duda alguna, las condiciones y medio ambiente de trabajo representan los cimientos de toda organización laboral, por eso la importancia de implementar normativas legales que fomenten la seguridad y salud en el trabajo.…”
unclassified